GAME METHOD WITH MEDIA CHART TABLE FROM USED ITEMS TO INCREASE MOTIVATION, INTEREST, AND RESULTS - Sulfemi, Wahyu Bagja; Fajartriani, Tia; Handayani, Trissia (JMIE (Journal of Madrasah Ibtidaiyah Education), 2021)
This class action research is a descriptive quantitative study conducted in class III Abu Bakar Ash-Shiddiq SDIT Al-Hamidiyah, amounting to 28 people consisting of 14 male students and 14 female students. This study aims to improve the learning outcomes of grade IV students at SDIT Al-Hamidiyah in Social Sciences subjects about the Nature Appearance and Socio-Cultural Diversity using the game method through the media chart tables of used goods. This research was conducted in two cycles. Data collected in this study are quantitative data in the form of student learning outcomes. In pre-cycle learning, 6 students (21%) and not yet 22 people (79%) had completed students. In cycle 1 learning, 11 students (39%) completed and 17 students (61%) were incomplete. Cycle 2 was completed 27 people (96%) and those who were not yet 1 person (4%). The results of the analysis of this study indicate an increase in student learning outcomes starting from cycle 1 39% to 96% in cycle 2. The results of the study can be concluded that the use of the game method with a chart table of used goods can increase motivation, interest, and social science education outcomes.